Main Newspapers in Spanish Press Market. Property, Media Groups and Structural Connections - Nogales Bocio, Antonia (2014)
This research analyzes the managerial structure of the principal general diaries of Spain from a critical perspective. We come into the structural connections between the Spanish groups of communication, seeing the links with other media, industrial, financial and political sectors. In the same way, we contemplate the international projections of these groups, especially to the rest of Europe and South America. We approach to the real issuers of the journalistic discourse and to the determinants that impede nowadays the real informative pluralism in the Spanish media system.